"The Boy Has to Be a Man in Order for Life to Start": AmaXhosa, Black Boyhood Studies, and the Anthropology of Boyhoods. Issue 2 (1st April 2022) - Qambela, Gcobani
ABSTRACT: Contemporary and historically focused social science studies of amaXhosa (Xhosa) men have focused predominantly on Xhosa men attaining manhood through ritualised initiation ( ulwaluko ) and heterosexual homemaking ( ukwakha umzi ). These studies have left critical knowledge gaps of the pre-initiation lives of Xhosa men throughout the lifecycle, along with processes of socialisation. Based on ethnographic fieldwork spanning over a year (2013–2014) conducted in rural and peri-urban Peddie in the Eastern Cape, my ethnography shows the necessity of examining the formation of Xhosa masculinities prior to ulwaluko. My research illustrates the importance of boyhood kwaXhosa. I argue that Xhosa masculinities are viable long before initiation and that it is not in manhood that "life" starts for men as one of my research interlocutors, Mthuthu, alluded. My ethnography necessarily challenges recent theorisations and conceptualisations of Xhosa masculinities as well as older canonical writings as far as they place primacy on the initiated Xhosa male phallus in the attainment of masculinity. I argue for scholarly consideration of the nuances and complexities of being a boy. Although there is a developing corpus of work from Black Boyhood studies, I note the limitations of this field especially for its rootedness in the North American Black boyhood experiences that do not have the cultural context of ulwaluko . Ultimately, I argue for an Anthropology of Boyhoods. Through concentrated effort on boyhood, in the study of masculinities, ultimately we can attain more contextual, varied and multifaceted experiences of how men experience masculinity across the life course.